2016
DOI: 10.3390/ijms17010058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chromatin Structure on the Extent and Distribution of DNA Double Strand Breaks Produced by Ionizing Radiation; Comparative Study of hESC and Differentiated Cells Lines

Abstract: Chromatin structure affects the extent of DNA damage and repair. Thus, it has been shown that heterochromatin is more protective against DNA double strand breaks (DSB) formation by ionizing radiation (IR); and that DNA DSB repair may proceed differently in hetero- and euchromatin regions. Human embryonic stem cells (hESC) have a more open chromatin structure than differentiated cells. Here, we study the effect of chromatin structure in hESC on initial DSB formation and subsequent DSB repair. DSB were scored by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 33 publications
(59 reference statements)
2
27
0
Order By: Relevance
“…In terms of DSB/Gy/Gbp, our findings show that more DSBs are produced in the euchromatin than in the heterochromatin but have similar complexities. These results conform to experimental biological observations on the role of chromatin compaction in the protection of DSB induction.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…In terms of DSB/Gy/Gbp, our findings show that more DSBs are produced in the euchromatin than in the heterochromatin but have similar complexities. These results conform to experimental biological observations on the role of chromatin compaction in the protection of DSB induction.…”
Section: Resultssupporting
confidence: 90%
“…Conversely, for alphas of 5.27 MeV, more DSB/kbp were observed in the euchromatin than in the heterochromatin, 0.0049 ± 0.0003 and 0.0045 ± 0.0004, respectively. Again, a time of 10 ns seems to be more suitable as it better reproduces the difference between condensed and decondensed chromatin, that is, more DSB damage in the euchromatin than in the heterochromatin as indicated in different studies …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Protection against unscheduled HR is particularly important in the case of DSBs occurring in the highly repeated sequences in the ribosomal DNA (rDNA) and pericentromeric regions, since such repair could lead to insertions, deletions, and chromosomal rearrangements. The notion of a protective role for HC is supported by a recent study analysing the production and repair of DSBs in human embryonic stem cells (hEScs) where the chromatin has a more open structure than that in differentiated cells [42]. It was observed that the same dose of radiation produced significantly more 53BP1-containing IRIF in hESCs than in normal fibroblasts, from which the authors concluded that DNA within HC may indeed be protected against damage.…”
Section: Dsbs and Heterochromatinmentioning
confidence: 99%